Challenges of Green Logistics in Southeast Europe - Beškovnik, Bojan; Jakomin, Livio (Promet - Traffic&Transportation, 2012)
This paper describes the trends towards green logistics in global aspect and challenges of adopting green logistics in the region of Southeast Europe. Modern logistics with supply chain management is experiencing a period of important evolution. From reversible logistics, we came to green logistics, which is a wider concept of environmentally friendly thinking. Reverse logistics includes processes of movements and transportation of waste from users to recycling plants; meanwhile, green logistics deals also with environmental issues such as pollution and environmental degradation caused by improper logistics processes and utilisation of old and environmentally unfriendly transport technology. The case of Southeast Europe was analysed, and in this context, a development model for green logistics implementation was proposed. A vast number of different challenges in the logistics sector are still open in this region; therefore, systematic analyses and proposals should be subject of additional scientific work in the logistics sector. All parties, including manufacturing industry, logistics providers and governments should take an active part in such researches, as the pressure from green thinking will become even stronger in the coming period. KEY WORDS: reverse logistics, green logistics, logistics providers, Southeast Europe, green logistics model